2021
DOI: 10.1038/s41598-021-88621-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of anxiety and depression among the community-dwelling elderly in Nay Pyi Taw Union Territory, Myanmar

Abstract: Providing elderly mental healthcare in Myanmar is challenging due to the growing elderly population and limited health resources. To understand common mental health problems among Myanmar elderly, this study explored the prevalence and risk factors of anxiety and depression among the elderly in the Nay Pyi Taw Union Territory, Myanmar. A cross-sectional study was conducted among 655 elderly by face-to-face interviews with a pretested questionnaire. Descriptive analysis and multiple logistic regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
15
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
8
15
0
4
Order By: Relevance
“…The higher prevalence of depression after retirement could be due to the fact that after they stop working, individuals may lose their social and psychological benefits of being active which in turn contribute to depression [ 67 ]. It is found that rural resident older adults were significantly at higher risk of experiencing depression than their urban resident counterparts and this evidence is supported by previous studies [ 63 , 73 ]. It is observed that urban resident older adults have higher access of healthcare services and social resources than rural areas.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The higher prevalence of depression after retirement could be due to the fact that after they stop working, individuals may lose their social and psychological benefits of being active which in turn contribute to depression [ 67 ]. It is found that rural resident older adults were significantly at higher risk of experiencing depression than their urban resident counterparts and this evidence is supported by previous studies [ 63 , 73 ]. It is observed that urban resident older adults have higher access of healthcare services and social resources than rural areas.…”
Section: Discussionsupporting
confidence: 83%
“…This study found that oldest-old respondents had lower depressive symptoms than their younger counterparts. People in older ages tend to have more experiences of negative emotions that lead to develop positive attitudes towards stressful events and increase their ability to fight health risks and have better mental health by utilizing available resources and services [ 73 ]. Concurrent with contemporary literature [ 6 , 63 ], our study also indicates that older women were more prone to have major depression than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults with a monthly income <2004 ETB were nearly 2 times more likely to have depression as compared to participants with an income of ≥2004 ETB. Similar to a finding of different studies reported in Asia (Myanma) [ 45 ], North Indians [ 11 ], and Portugal [ 46 ]. This is the finding that low-income people have more difficult getting healthy services and care, which has been associated with higher levels of depression.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, younger members should venerate and care for elderly members. Thus, Chinese elderly adults are particularly worried about illness or poverty from which they may fail to support and lead the family or become a heavy burden to their children for physical illness and low social-economic status ( 47 ). In this reactive chain, elderly adults' great concerns for the family can strengthen their nervousness about imminent issues.…”
Section: Discussionmentioning
confidence: 99%